Thermoelectric efficiency of anisotropic materials with an application in layered systems - Shi, Wencong (2023)
Thermoelectric (TE) transport in anisotropic materials is investigated based on most general thermodynamical concepts. Currents and power conversion efficiency are studied in SnSe and SnS in different directions. The design of composites whose TE performance along different principles directions is the same is proposed. Although such features do not occur naturally, such man-made anisotropic materials can be constructed using bilayers achieving much broadened working conditions of TE conversion devices. Intricate relationships between the anisotropy and the direction of the electric and heat currents are revealed, which further help us understand how transport occurs in such composites.